Perencanaan Strategis dalam Rangka Pengembangan Sumber Daya Manusia (SDM) di Universitas Islam “45” (UNISMA) Bekasi - Nor Khakim (LPPM STKIP Kusuma Negara, 2016)
This research was scintifically purposed to support Strategic Planning Accountability of Human Resources at Unisma Bekasi. This research used qualitative method by technique to collect the data’s interview is used for the rector, rector assistants, lecturers, and employees. The observation is done directly to find out the information and the result of interview. The study gives description about the strategic planning accountability through 7 goals of institusional and the empowering human resources academic duty performance under efficiency internal control such as, lecturers’ career, promotion, rewrad and scholarships for education. The empowering human resources was done by human capital management. It can be concluded that Unisma Bekasi University has been increasing of academic duty performace in all of the sectors. And then realisation strategic planning accountability of empowering human resources the goal together in the university. Then also the rector in the arrangement for education human resources are done quaranted all sectors of academic duty performance as well. The essay above can be found that the strategic planning accountability of empowering human resources increase the academic duty performance for internal sector in Unisma Bekasi University that been realized to optimal